The Influence Of Debt Financing, Equity Financing, And Non Performing Financing On The Financial Performance Of Sharia Commercial Banks In Indonesia For The 2017-2022 Period - Hasanah, Annisa Javalia; Marliyah, Marliyah; Daulay, Aqwa Naser (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
In the 2017-2022 period, the financial performance of Sharia Commercial Banks in Indonesia is influenced by debt financing, equity financing and non-performing financing (NPF). Increasing use of debt and equity also increases NPF. This is a challenge in bank credit risk management. This quantitative research uses multiple regression analysis methods and panel data, using Eviews 10 software. The aim of this research is to discover and analyze how the variables of debt financing, equity financing and bad credit have an impact on the financial performance of Sharia Commercial Banks in Indonesia from 2017 to 2022. The research results show that debt financing has a positive influence on ROE. Meanwhile, equity financing and non-performing financing (NPF) have a negative influence on the financial performance (ROE) of Islamic Commercial Banks in Indonesia at the same time. This shows that with good management of credit financing, profit-sharing financing, and bad credit in sharia banks, including Murabahah schemes for buying and selling transactions, Mudharabah and Musyarakah for profit sharing models, as well as special mechanisms to handle payment difficulties by customers according to the principles sharia, able to maintain adequate capital so that sharia bank equity can increase.